Religion and Pluralistic Co-Existence, The Muhibbah Perspective (A Collection of Seminar Papers) - Kamar Oniah Kamaruzaman (IIUM Press, 2010)
This book is a collection of 15 papers presented in seminars on the themes of pluralistic co-existence, religion, interfaith initiatives, justice and peace. The 15 papers are grouped into 3 sections. Section 1 adresses the issue of religion in a pluralistic society. Section 2 is on interfaith initiatives where interfaith dialogue and engagement are defined as well as the premises and the etiquettes of interfaith initiatives, the what and the how, the do's and the don'ts, the aptitude and the attitude of those participating in such initiatives. Section 3 is on social responsibilities, justice and peace. This section is in fact an attempt to promote social responsibilities as personal responsibilities where everyone has a role and a responsibility towards this nation and this world. Indeed, the pains and miseries abound are not so much the reflection of the successes and the triumphs of the bad and evil but are more so testimonies of the failure of the good and the conscientious to affect goodness into society. We are born as we and in this Age because we have roles and responsibilities as we are towards our Age. Indeed, no one is so humble so as to be irrelevant, and no good deed is ever redundant so as to be meaningless, and no kindness is ever so insignificant so as to be wasted.CONTENTS